Revision of the bamboo leafhopper tribe Mukariini (Hemiptera: Cicadellidae: Deltocephalinae) from the Indian subcontinent with description of new genera and species - Viraktamath, C.a.; Webb, M.d. (Zootaxa, 2019)
Leafhopper genera and species of the tribe Mukariini from the Indian subcontinent are revised. Nine genera and 22 species including two new genera, one new subgenus and 12 new species are dealt with. The new taxa described are Aalinga gen. nov. with its type species Aalinga brunoflava sp. nov. (India: Andaman Islands), Buloria indica sp. nov. (India: Karnataka). Buloria zeylanica sp. nov. (Sri Lanka), Flatfronta bella sp. nov. (India: Karnataka; Bangladesh), Mohunia bifurcata sp. nov. (Myanmar), Mukaria omani sp. nov. (India: Gujarat, Karnataka, Madhya Pradesh), Mukaria vakra sp. nov. (India: Karnataka), Mukariella gen. nov. with its type species Mukariella daii sp. nov. (India: Manipur), Myittana (Benglebra) cornuta sp. nov. (India: Karnataka), Myittana (Myittana) distincta sp. nov. (India: Karnataka), Myittana (Savasa) subgen. nov. with its type species Myittana (Savasa) constricta sp. nov. (India: Andhra Pradesh, Gujarat, Haryana, Himachal Pradesh, Karnataka, Madhya Pradesh, Punjab, Tamil Nadu, Uttarakhand) and Scaphotettix arcuatus sp. nov. (India: West Bengal, Meghalaya, Mizoram). Genera Buloria Distant (new placement), Crispina Distant (new placement) and Myittana Distant (new placement) are placed in the tribe Mukariini. Genus Mohunia is redefined based on the study of its type species. Benglebra Mahmood & Ahmed 1969 is synonymised with Myittana Distant 1908 and considered as its subgenus. Myittana (Benglebra) alami (Mahmood & Ahmed) comb. nov., Myittana (Savasa) bipunctata (Mahmood & Ahmed) comb. nov.. Myittana (Benglebra) introspina (Chen & Yang 2007) comb. nov. and Mukariella bambusana (Li & Chen) comb. nov. are proposed; the first two species were earlier placed in the genus Benglebra, the third species in the genus Mohunia and the fourth in the genus Mukaria. Genera Flatfronta Chen & Li and Myittana are new records for India and Scaphotettix striata Dai & Zhang is a new record for the Indian subcontinent and Sri Lanka. All taxa dealt with are described and illustrated and keys for genera and their species are also given.